Socio-cultural Transformations in Traditional Societies in the Context of Globalization - Abdulaeva, E S; Yarychev, N U; Abdulvahabova, B B; Eskerkhanova, L T; Vakhabova, S A (KnE Social Sciences, 2019)
The paper presents a study of socio-cultural transformations in traditional societies in the context of globalization. The authors emphasize that global changes have affected all aspects of traditional societies using the socio-cultural approach. Postmodern culture, the problems of self-identification at different levels of the human community are the main consequences of globalization. The differences between the social strata are leveled through the introduction of a mass unified consumerism culture, desubjectivation of the individual and public institutions takes place. The social space has changed, the forms of human interaction with the external environment and interpersonal communications have changed. Previously existing models of communications, which were direct interpersonal relations, were replaced in the modern world by forms of mediated communication. They bring new patterns of behavior and understanding of sociocultural reality. Changing the traditional family as an important subject of socialization and translation of spiritual values leads to further transformations in society. Keywords: sociocultural transformations; values; globalization; society; traditions.